2013
DOI: 10.1007/s00114-013-1090-x
|View full text |Cite
|
Sign up to set email alerts
|

Bechstein’s bats maintain individual social links despite a complete reorganisation of their colony structure

Abstract: Several social mammals, including elephants and some primates, whales and bats, live in multilevel societies that form temporary subgroups. Despite these fission-fusion dynamics, group members often maintain long-term bonds. However, it is unclear whether such individual links and the resulting stable social subunits continue to exist after a complete reorganisation of a society, e.g. following a population crash. Here, we employed a weighted network analysis on 7,109 individual roosting records collected over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 15 publications
1
25
0
Order By: Relevance
“…In systems smaller than N crit , on the other hand, we could show that even induced group structures cannot be transformed into long-term community structures. This agrees with empirical observations that report the absence of such community structures in small colonies Baigger et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In systems smaller than N crit , on the other hand, we could show that even induced group structures cannot be transformed into long-term community structures. This agrees with empirical observations that report the absence of such community structures in small colonies Baigger et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…The question is how this dynamics relates to other dynamical processes observed in the colony on longer time scales. Specically, Kerth et al (2011) and Baigger et al (2013) already reported that the long-term social network of larger colonies of Bechstein's bats consists of communities. These are quite stable social structures that can be detected over years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They refer to the same colony, BS, but to dierent years, 2007 and 2011. We observe that the size and the composition of the colony has changed drastically, due to external inuences and birth/death processes (Baigger et al, 2013;Fleischer et al, 2017). Table 1 gives an overview of the size of the L/F networks for the dierent years.…”
Section: Eventsmentioning
confidence: 98%
“…Baigger et al . () took advantage of a population crash (65% decline) in an intensively studied maternity colony of Bechstein's bat Myotis bechsteinii to evaluate stability of social subunits following a crash and found that the colony's two stable social subunits fused into a non‐modular social network. However, long‐term bonds identified prior to the crash were still detectable after the crash, suggesting that bats retain a memory for previous individual relationships following a reorganization of social structure (Baigger et al ., ).…”
Section: Introductionmentioning
confidence: 99%